2014
DOI: 10.2754/avb201483030219
|View full text |Cite
|
Sign up to set email alerts
|

The effect of manganese supplementation on its concentrations in blood, hair, and organs of goat kids

Abstract: The aim of this study was to evaluate the effect of supplementation with an organic form of manganese on its concentration in blood, hair, and organs of goat kids. A total of 27 kids were divided into control and experimental groups on the day of their birth (Day 1). The kids were on mother's milk only diet until the day of weaning (Day 70). After weaning the kids received pellets at doses 0.3 kg/head/day for next 70 days. The control group received pellets (manganese content 36.7 mg/kg) and the experimental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Possible reasons may be that they form fewer complexes with other components of food, or they are less likely to cause adverse effects in the digestive tract [ 9 ]. The organic forms of Mn could have a more extensive use, and therefore, they can be added in smaller amounts to feed, since such Mn is more absorbed and is also less likely to be removed from the body, thus leading to less accumulation in the environment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Possible reasons may be that they form fewer complexes with other components of food, or they are less likely to cause adverse effects in the digestive tract [ 9 ]. The organic forms of Mn could have a more extensive use, and therefore, they can be added in smaller amounts to feed, since such Mn is more absorbed and is also less likely to be removed from the body, thus leading to less accumulation in the environment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Fathy Nawito et al (2015) demonstrated Fe, Cu and Zn levels as 4.91±0.09 ppm, 0.49±0.05 ppm, 4.65±0.24 ppm in non-pregnant goats reared in South Sinai, Egypt, respectively. In a study on experimental doses of Mn in kids, the average of blood Mg level of 140 th day was 3.14±0.19 mg/kg in the control group (Pitropovska et al, 2014). In another study where high dose of Pb investigated, Pb levels of blood in Red Sokoto goats grazed freely on open pastures in Zaria changed between 0.26 mg/L and 1.56 mg/L while the mean value of 0.89±0.43 mg/L.…”
Section: Discussionmentioning
confidence: 97%
“…Hair analysis has been studied in various animal species: livestock (Combs 1987;Christodoulopoulos et al 2003;Cygan-Szczegielniak et al 2014), sheep (Hawkins and Ragnarsdottir 2009), goats Pitropovska et al 2014 SD -standard deviation, C -colour; * Significance P ≤ 0.05, *** Significance P ≤ 0.001, ns -not significant , camels (Faye and Seboussi 2009), mule deer (Roug et al 2015), horse (Dunnett and Lees 2003;Asano et al 2005) and seals (Ikemoto et al 2004). Some of these studies show the diagnostic potential of hair analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Roug et al (2015) report a Mn concentration of 0.02-120.0 mg/kg DM in mule deer hair. Pitropovska et al (2014) found 3.14 ± 0.19 and 4.25 ± 0.36 mg/kg DM in kids of white short haired goats with different supplementations of manganese. These lower values are corresponding with our values for white haired llamas, supporting our finding of a significant effect of colour on the concentration of Mn in hair.…”
Section: Manganesementioning
confidence: 92%
See 1 more Smart Citation